Effect of subsurface damage on tensile behavior and fracture mechanism of SiCp/Al composites: Experimental analysis and RVE modeling. (May 2023) - Gao, Lei; Liu, Chang; Liu, Junjie; Yang, Tao
Graphical abstract: Highlights: Subsurface damage (SSD) adversely affects mechanical properties of material. RVE model considering SSD damage of SiCp/Al composite is established. Particle fracture and debonding in SSD area cause crack initiation and propagation. ε xx and ε yy in high and low stress state, respectively are sensitive to SSD depth. Fracture mechanism of SiCp/Al/45% composites containing SSD is revealed. Abstract: Machining-induced subsurface damage (SSD) is crucial for the reliable application of composite components. This paper investigated the SSD characteristics and its effect mechanism on tensile behavior and fracture mechanism for SiCp/Al/45%p based on experimental analysis and numerical modeling. Specifically, a representative volume element (RVE) model considering SSD was established to reveal the crack initiation and propagation in uniaxial tension. The digital image correlation (DIC) technique was used for monitoring the tensile strength and full-field strain of specimens containing SSD. The results showed that the increase in SSD depth decreases the tensile strength, which declined by 16.3% from 258 MPa to 216 MPa when SSD depth increased from 60 μm to 210 μm. The ε xx maximum negative strain in the high-stress state and the ε yy maximum positive strain in the low-stress state were susceptible to increased SSD depth. The fractography characteristics analysis showed the initial fracture position of the specimens was within the SSD area. The brittle fracture of particles and ductile fracture of the matrix are the main fracture mechanisms of SiCp/Al/45%p. A few particle-matrix interface failure was observed. Moreover, the RVE model indicates that the location of particle fracture and particle debonding damage is prone to generate stress concentrations, leading to crack initiation and propagation. This study provides a new sight and theoretical guidance for the reliability application SiCp/Al composite.